The Effect of Applying Argument Driven Inquiry Models to the Critical Thinking Skills of Students Based on Gender Differences - Laya Nazila; Undang Rosidin; I Wayan Distrik; Kartini Herlina; Neni Hasnunidah (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2019)
This study aims to determine the effect of the application of the Argument-Driven Inquiry (ADI) learning model on students' critical thinking abilities and to determine the differences in critical thinking skills between female and male students in the class using the learning model Argument-Driven Inquiry (ADI). The subjects of this study were students of class VIII.1 and VIII.5 JHS 13 Bandarlampung, consisting of 30 students of class VIII.1 and 30 students of class VIII.5. The sample was taken using a purposive technique by looking at the class with the same number of female and male students. The research design used was quasi-experimental design with Pretest-posttest Control Group Design and data collection techniques of critical thinking skills using pretest-posttest, which refers to the five criteria of critical thinking according to Ennis. The results showed that (1) there is an effect of applying the Argument-Driven Inquiry learning model on female students' critical thinking skills as indicated by the sig value. equal to 0,0001 (2) there is an effect of the application of the Argument-Driven Inquiry learning model on male students' critical thinking skills as indicated by the sig value. for 0,000 (3) there is no difference in critical thinking skills between female and male students using the ADI model indicated by the sig value and amounting to 0.725. That is, the application of the Argument-Driven Inquiry model affects the critical thinking skills of both female and male students, but there is no difference in critical thinking skills between female and male students. This means, the implementation of Argument-Driven Inquiry model effective on students’ critical thinking skill, but there is no difference in critical thinking skills between female and male students.